1997
DOI: 10.1097/00007890-199704270-00018
|View full text |Cite
|
Sign up to set email alerts
|

Engrafted Human T and B Lymphocytes Form Mixed Follicles in Lymphoid Organs of Human/Mouse and Human/Rat Radiation Chimera1

Abstract: The different homing patterns exhibited by the T and B lymphocytes indicate that the homing receptors on human B cells might be cross-reactive with their mouse counterparts, in contrast to the human T cells, which seem to be unable to interact with the mouse homing receptors. The presence of human B and T lymphocytes in close proximity to each other in the lymphoid tissues is in accordance with the ability of human/BALB radiation chimera to mount significant primary human antibody responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Meaningfully, the human T lymphocytes, recovered from Trimera mice within the first month posttransplantation, retain their proliferative capabilities and can mount primary anti‐HIV‐1 cellular immune responses, such as IFN‐γ secretion after their in vitro exposure to an HIV‐1 specific immunogen. The relatively rapid induction of humoral and cellular immune responses may be partially explained by the xenoactivation of the engrafted human cells and by the close proximity between T and B cells in the normal microenvironment of the mouse lymphoid tissues (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meaningfully, the human T lymphocytes, recovered from Trimera mice within the first month posttransplantation, retain their proliferative capabilities and can mount primary anti‐HIV‐1 cellular immune responses, such as IFN‐γ secretion after their in vitro exposure to an HIV‐1 specific immunogen. The relatively rapid induction of humoral and cellular immune responses may be partially explained by the xenoactivation of the engrafted human cells and by the close proximity between T and B cells in the normal microenvironment of the mouse lymphoid tissues (27).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, we have demonstrated that the human engrafted cells can elicit primary and secondary anti‐HIV‐1 humoral and cellular immune responses. It has already been demonstrated that the engrafted human cells, which are engrafted in significant numbers and are found in different internal organs for at least 2 months (20, 21, 27), are in a nonanergized functional status, can form mixed lymphoid follicles similar to germinal centers (27), and can mount primary humoral (26) and cellular (25) human immune responses. The capacity of the engrafted human T and B cells to be in close proximity to each other in the normal microenvironment of the mouse lymphoid tissues (27) is probably crucial for the generation of the human primary and secondary Ab response, here manifested by the initial production of anti‐HIV‐1 IgM isotype Abs followed by production of anti‐HIV‐1 IgG isotype Abs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known as Trimera or humanized mice. The chimera mice has engrafted with peripheral blood mononuclear cells (PBMCs) in Balb/c mice, which have already lethally irradiated and transplanted by the bone marrow of NOD (knockout mice) mice [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Since these chimera contain tissues from three different sources (murine recipient, SCID mouse BM donor, human PBMC donor), the mice were termed trimera 17. Due to the existence of preformed murine lymphatic organs, the engraftment of transferred human T and B cells reaches its peak already within the first 3 weeks post‐transplant with formation of lymphoid follicles in peritoneum, lymph nodes and spleen 16, 18. Moreover, high numbers of human lymphocytes can be transplanted into different strains of mice without the complications of GvHD or EBV lymphomas 19.…”
Section: Introductionmentioning
confidence: 99%